Evaluating Corporate Financial Performance: A Profitability Ratio Approach - Aurelia Widya Astuti; Kiflu Chekole Tekle; Alemayehu Abera Lema; Diana Magfiroh (Al-Makki Publisher, 2025)
Corporate financial performance evaluation is essential for guiding strategic decision-making by managers, investors, and stakeholders, yet raw financial data alone provides limited insight without a structured interpretive framework. This study aims to evaluate the financial performance of PT Dunia Virtual Online Tbk by applying four profitability ratios Gross Profit Margin (GPM), Net Profit Margin (NPM), Return on Assets (ROA), and Return on Equity (ROE) simultaneously within a unified analytical framework. A descriptive quantitative research design was employed, with data sourced from the company's audited financial statements for the period ending 31 March 2025. Each ratio was calculated using standardized formulas derived from the income statement and balance sheet, encompassing net sales of IDR 14,567,561,590, cost of goods sold of IDR 6,917,131,209, net income of IDR 2,028,267,985, total assets of IDR 301,240,237,537, and total equity of IDR 234,410,798,865. The results show that GPM reached 52.52%, reflecting strong production cost efficiency; NPM was recorded at 13.92%, indicating effective overall cost management; while ROA and ROE were notably low at 0.67% and 0.87% respectively, suggesting that the company's substantial asset and equity base has not yet been fully optimized to generate proportional returns. These findings reveal a dual performance profile: high operational efficiency at the production and cost management level, contrasted with low capital utilization efficiency—consistent with characteristics of a company in an active investment and asset accumulation phase. This study concludes that an integrated multi-ratio approach yields a more comprehensive and diagnostically precise assessment of corporate financial health than single-indicator analysis, offering actionable insights for both internal management and external investors.